Epistemologies, methodologies and theories used in qualitative Global North health and social care research: a scoping review protocol - Julie Taylor; Caroline Bradbury-Jones; Oliver Rudolf Herber; Cynthia Okpokiri (BMJ Open, 2025)
Introduction In qualitative research, there are different approaches to defining and engaging with social reality. Epistemology, as the study of knowledge and knowledge creation, influences the methodologies and theories used by researchers. A growing literature questions the universality of Western-centric and Global North research methodologies and theories and highlights their Western epistemological roots. While Western frameworks are appropriate for Western contexts, it is a fallacy to assume that they represent global realities, thereby marginalising Global South knowledge systems. Thus, the aim of this scoping review is to analyse the underlying epistemologies, methodologies or theories that are evident in qualitative research conducted by researchers from the Global North in their research on, for or with people from the Global South.Methods and analysis The review will be conducted using the Joanna Briggs Institute framework for scoping reviews. A search strategy will be developed to identify published and unpublished literature in CINAHL, Embase, Google Scholar, MEDLINE, ProQuest, PsycINFO and Web of Science. All potential papers will be exported to the reference manager Zotero, and the results will be uploaded to Rayyan. Studies are selected using a three-step process and documented using the Preferred Reporting Items for Systematic Reviews and Meta-Analyses flowchart. The abstracted studies will then be collated using the PAGER framework to identify the patterns, advances, gaps, evidence and recommendations that help to understand the review question.Ethics and dissemination As this is a secondary analysis, our research does not require ethical approval, but we will scrutinise all included studies for inclusion of an ethical approval statement. We intend to share our findings through peer-reviewed international journals and presentations at conferences, as well as collaborating with colleagues in related fields.Study registration The protocol for this scoping review has been registered with the Open Science Framework (https://doi.org/10.17605/OSF.IO/5BUZX).